Force Interaction of the Current-Carrying Systems and Ponderomotive Effects of Electromagnetic Waves (Global Journal of Science Frontier Research, 2018)
From the times of Lorenz and Poincare the Lorentz force was introduced as experimental postulate, and up to now there was no explanation of its physical nature. in the article is proven that the Lorentz force is the consequence of the dependence of the scalar potential of charge on the speed. This made possible to explain physics of power interaction of the current carrying systems, and also operating principle of unipolar generators. It is shown also, that the ponderomotive action of electromagnetic waves is the consequence of the dependence of the scalar potential of charge on the speed, but not by the consequence of the fact that, as it was considered earlier, electromagnetic wave possesses mechanical impulse.
Keywords: maxwell's equation; lorentz force; scalar- vector potential; ponderomotive force